EXAMINATION OF MUSLIM CONSUMERS’ INTENTIONS TO EAT AT FINE DINING RESTAURANTS - Muhammad Amiruddin Al- Farisi; Latifah Putranti; Nuraini Desty Nurmasari (Journal of Islamic Monetary Economics and Finance, 2021)
This paper aims to identify the functional, symbolic, hedonic and Islamic value constructs of Muslim consumers’ satisfaction with fine dining restaurants. In addition, it develops the role of religiosity in the relationship between hedonic and Islamic symbolic values ​​in consumer satisfaction and examines the effect of such satisfaction on the willingness to pay more. The method used in the research is based on a Structural Equation Modeling (SEM), with data collected using a questionnaire; 281 valid respondents took part in the study. The results show that in terms of the influence of the dimensions of perceived value in explaining customer satisfaction, the functional, hedonic and Islamic have has a positive and significant effect, whereas the symbolic value variable is is perceived to have no significant effect on satisfaction. Furthermore, customer satisfaction has a significant positive effect on the willingness to pay more. In comparison, religiosity does not moderate the effect of perceived symbolic value on consumer satisfaction. However, it does moderate the effect of hedonic and Islamic value.